Self-extension and a quasi-other as fundamental concepts of postphenomenological approach of the philosophy of technology - Verashchaka, Aliaksei I. (Journal of the Belarusian State University. Philosophy and Psychology, 2021)
The article covers the analysis of the major categories of postphenomenological approach of the philosophy of technology. The following concepts are considered: «technological background», «quasi-other» and «self-extension». By means of numerous examples the insight of the transformation of human experience, mediated by technical objects, is revealed in detail. The ontological relation between man and technology is indentified, in which the latter acts as an intermediary between the cogniser and the world. The insight into the neutrality of technology in the instrumentalist approach of the classical philosophy of technology is challenged. The essential role of technology and computing in the formation of the modern scientific worldview and civilisation as a whole is emphasised.
Keywords: the philosophy of technology; ontology of technology; philosophy of science; instrumentalism; neutrality of technology; machine background; mediator; technical object; lifeworld; perceivement; transformation of experience